Halogen adsorbent

The combination of zinc with calcium aluminate and silica in an adsorbent significantly enhances halogen adsorption, overcoming the inefficiencies of existing adsorbents and addressing environmental and catalytic challenges.

JP2025050567APending Publication Date: 2025-04-04JGC CATALYSTS & CHEMICALS LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023159431
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing adsorbents are not effective in adsorbing a large amount of halogens, which are commonly found in flame retardants and other chemical substances, posing environmental and catalytic poisoning issues.

Method used

An adsorbent containing zinc as the primary halogen adsorbing component, combined with calcium aluminate and silica, which significantly enhances the halogen adsorption capacity compared to adsorbents using either calcium aluminate or silica alone.

Benefits of technology

The adsorbent achieves a substantial increase in halogen adsorption, effectively addressing the limitations of existing technologies and reducing the risk of catalyst poisoning and environmental contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050567000001_ABST
    Figure 2025050567000001_ABST
Patent Text Reader

Abstract

To provide an adsorbent with a large amount of halogen adsorption.SOLUTION: An adsorbent contains zinc as a component adsorbing halogen, and furthermore contains calcium aluminate and silica. Ca / Al2 molar ratio is 1.5 or less. Si content is within the range of 10 mass% or more and 60 mass% or less for the total amount of halogen adsorbent in terms of SiO2. Zn content is within the range of 30 mass% or more and 80 mass% or less for the total amount of the halogen adsorbent in terms of ZnO.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adsorbent for removing halogens. [Background technology]

[0002] Halogen is a general term for halogen elements such as fluorine (F), chlorine (Cl), bromine (Br), and iodine (I). Since its compounds are chemically stable, they are widely used in applications such as flame retardants that make flammable materials such as plastics less flammable. On the other hand, chlorine, bromine, and the like are components of chemical substances with high ecotoxicity such as dioxins and polychlorinated (brominated) biphenyls, and advanced processing technology is required when disposing of plastics containing these. In addition, since halogens are one of the substances that cause deterioration of plant piping, etc., technology to remove halogens is also required when reusing plastics containing halogens (Non-Patent Document 1). Furthermore, since halogens are poisonous substances for catalysts, technology to remove halogens from raw materials is used in fields that use catalysts (for example, the oil refining field) (Patent Documents 1 to 4).

[0003] As one of the techniques for removing halogens, there is known a technique for removing halogens by adsorbing them with an adsorbent, as described in Patent Document 1. There is a demand for an adsorbent capable of adsorbing a larger amount of halogens as an adsorbent for use in such a technique. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-72984 A [Patent Document 2] JP 2008-184512 A [Patent Document 3] Patent Publication No. 2021-7937 [Patent Document 4] Special Publication No. 2018-523572 [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Waste Management and Resource Circulation, Vol.29, No.2, pp.152-162, 2018 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an adsorbent having a large halogen adsorption capacity. [Means for solving the problem]

[0007] The present inventors have found that the amount of halogen adsorbed is increased by using an adsorbent that contains Zn as a component that adsorbs halogens and further contains calcium aluminate and silica. Effect of the Invention

[0008] According to the present invention, an adsorbent having a large halogen adsorption amount can be provided. [Brief description of the drawings]

[0009] [Figure 1] 1 shows X-ray diffraction patterns of the adsorbents obtained by the methods of Example 1 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention includes an invention relating to a halogen adsorbent (hereinafter, also referred to as "the adsorbent of the present invention"). The adsorbent of the present invention will be described in detail below.

[0011] [Adsorbent of the present invention] The adsorbent of the present invention contains zinc as a halogen adsorbing component, calcium aluminate and silica. The adsorbent containing zinc as a halogen adsorbing component and further containing both calcium aluminate and silica has a significantly higher halogen adsorption amount than an adsorbent containing either calcium aluminate or silica. Calcium aluminate is a general term for a compound obtained by mixing calcium oxide and aluminum oxide and heating the mixture at high temperature, and has the general formula xCaO·yAl 2 O 3 It is known that calcium aluminate can have various crystal structures depending on the ratio of x and y, and the presence or absence of calcium aluminate can be determined by the presence or absence of X-ray diffraction peaks derived from these crystal structures.

[0012] The molar ratio of calcium to aluminum (Ca / Al 2 The Ca / Al molar ratio is preferably 1.5 or less, more preferably in the range of 0.1 to 1.5, and particularly preferably in the range of 0.5 to 1.5. 2 The adsorbent of the present invention having a molar ratio within the above range exhibits a larger halogen adsorption amount.

[0013] The Si content of the adsorbent of the present invention is SiO 2 In terms of conversion, the Si content is preferably in the range of 10% by mass or more and 60% by mass or less, more preferably in the range of 15% by mass or more and 60% by mass or less, and particularly preferably in the range of 20% by mass or more and 60% by mass or less. The adsorbent of the present invention having a Si content in the above-mentioned range has a larger halogen adsorption amount. In addition, when chlorine is adsorbed as a halogen, the deliquescence of zinc chloride generated by the reaction of zinc and chlorine can be suppressed. The adsorbent in which zinc chloride has deliquesced is not preferable because it is stuck in the reactor and difficult to remove.

[0014] The Zn content of the adsorbent of the present invention is preferably in the range of 30% by mass or more and 80% by mass or less, more preferably in the range of 30% by mass or more and 75% by mass or less, and particularly preferably in the range of 30% by mass or more and 70% by mass or less, calculated as ZnO based on the total amount of the halogen adsorbent. The adsorbent of the present invention having a Zn content in the above range has a larger halogen adsorption amount. In addition, deliquescence due to the generation of zinc chloride is unlikely to occur.

[0015] The sum of the Ca content and the Al content of the adsorbent of the present invention is expressed as CaO equivalent and Al content, respectively, based on the total amount of the halogen adsorbent. 2 O 3 In terms of conversion, the sum is preferably in the range of 5 mass % or more and 40 mass % or less, more preferably in the range of 5 mass % or more and 30 mass % or less, and particularly preferably in the range of 5 mass % or more and 20 mass % or less. When this sum is in the above-mentioned range, the adsorbent of the present invention has a larger halogen adsorption amount.

[0016] The molar ratio of zinc to silicon (Zn / Si molar ratio) contained in the adsorbent of the present invention is preferably in the range of 0.1 to 3, preferably 1.5 or less, more preferably 0.1 to 2.5, and particularly preferably 0.1 to 2. The adsorbent of the present invention having a Zn / Si molar ratio in the above-mentioned range has a larger halogen adsorption amount.

[0017] The specific surface area of ​​the adsorbent of the present invention is 40 m 2 / g or more, 200m 2 / g or less, and 2 / g or more, 175m 2 / g or less, and more preferably 40m 2 / g or more, 150m 2 It is particularly preferable that the specific surface area is in the range of 1 / g or less. The adsorbent of the present invention having a specific surface area in the above-mentioned range has a larger halogen adsorption amount. The specific surface area in the present invention refers to the specific surface area determined by the BET point method.

[0018] The pore volume of the adsorbent of the present invention is preferably in the range of 0.45 mL / g or more and 1.0 mL / g or less, more preferably in the range of 0.45 mL / g or more and 0.9 mL / g or less, and particularly preferably in the range of 0.45 mL / g or more and 0.8 mL / g or less. The adsorbent of the present invention having a pore volume in the above-mentioned range has a larger halogen adsorption amount when adsorbing halogen contained in a liquid. The pore volume in the present invention refers to the total pore volume of the pore distribution obtained by mercury intrusion porosimetry.

[0019] The bulk density of the adsorbent of the present invention is preferably 1 g / mL or less, more preferably 0.9 g / mL or less, and particularly preferably 0.8 g / mL or less. The adsorbent of the present invention has a large halogen adsorption capacity, so that it can efficiently adsorb halogen even if the bulk density is low.

[0020] The shape of the adsorbent of the present invention may be spherical, columnar (including cylindrical and four-lobe) or similar. The size (the minimum length of the outer shape of the adsorbent) is preferably in the range of 0.5 mm to 6 mm. If the size of the adsorbent is small, the contact area between the adsorbent and the hydrocarbon increases, and the adsorption rate of halogen contained in the hydrocarbon increases.

[0021] The adsorbent of the present invention can remove halogens contained in various media and can more efficiently remove halogens contained in hydrocarbon process streams. The media can be liquid or gas. The adsorbent of the present invention can more efficiently remove halogens even from liquids, which tend to have lower halogen removal efficiency than gases.

[0022] [Method of producing the adsorbent of the present invention] The adsorbent of the present invention can be prepared, for example, by using a production method including the following steps (1) to (3).

[0023] (1) A shaped precursor preparation step of mixing a zinc source, calcium aluminate, and silica to prepare a shaped precursor. (2) A molding step of forming the shaped precursor into pellets to obtain an adsorbent precursor. (3) A calcination step of calcining the adsorbent precursor at a temperature of 300° C. or more and 500° C. or less to obtain an adsorbent.

[0024] Hereinafter, the method for producing the adsorbent of the present invention will be described in detail by taking this production method as an example, but the production method for the adsorbent of the present invention is not limited to this production method.

[0025] [(1) Molding precursor preparation process] The method includes a shaped precursor preparation step of mixing a zinc source, calcium aluminate, and silica to prepare a shaped precursor, in which a clay-like kneadate containing each of the components of the adsorbent of the present invention is prepared.

[0026] The mixing ratio of the zinc source in this step is preferably in the range of 30% by mass or more and 80% by mass or less, more preferably in the range of 30% by mass or more and 75% by mass or less, and particularly preferably in the range of 30% by mass or more and 70% by mass or less, based on the total amount of solids excluding the solvent. Zinc oxide, zinc carbonate, etc. can be used as the zinc source. Furthermore, the mixing ratio of calcium aluminate in this step is preferably in the range of 5% by mass or more and 40% by mass or less, more preferably in the range of 5% by mass or more and 30% by mass or less, and particularly preferably in the range of 5% by mass or more and 20% by mass or less, based on the total amount of solids excluding the solvent. Furthermore, the mixing ratio of silica in this step is preferably in the range of 10% by mass or more and 60% by mass or less, more preferably in the range of 15% by mass or more and 60% by mass or less, and particularly preferably in the range of 20% by mass or more and 60% by mass or less, based on the total amount of solids excluding the solvent. The zinc source, calcium aluminate and silica used in this step may be either commercially available products or synthetic products.

[0027] In this step, in addition to the aforementioned components, a solvent is mixed. This solvent is a component for fixing the aforementioned components together to form a precursor suitable for molding. In this step, both inorganic and organic solvents can be used as the solvent, and it is preferable to use an inorganic solvent, and it is more preferable to use water. The mixing ratio of the solvent varies depending on the properties of the aforementioned components, and it is difficult to determine a preferred range, but it is preferable to mix it so that it is in the range of 1% by mass or more and 50% by mass or less with respect to the total amount of the molding precursor. If the amount of solvent added is small, the aforementioned components tend to stick together and become granular, and such a molding precursor can be suitably used as a precursor for tablet molding. Also, if the amount of solvent added is large, the aforementioned components tend to stick together and become clay-like, and such a molding precursor can be suitably used as a precursor for extrusion molding. In addition, the solvent contained in the silica sol is also included in the aforementioned solvent.

[0028] In this step, the components can be mixed by a conventional method. For example, they can be mixed using a high-speed mixer, a mill, or the like. They can also be mixed using a kneader. These mixing methods can be appropriately selected so as to match the production process.

[0029] [(2) Molding process] In this step, the molded precursor obtained in the above step can be molded using a conventionally known method. For example, it can be molded into pellets using tablet molding, extrusion molding, etc. When using tablet molding, it is recommended to use a method in which the granular molded precursor is set in a tablet molding machine and a certain pressure is applied. The shape of the adsorbent finally obtained can be determined by the shape of the cylinder used. In addition, when using extrusion molding, it is recommended to use a single-axis auger type extruder or a disk pelleter for the clay-like molded precursor. The shape of the adsorbent finally obtained can be determined by the shape of the die used. The adsorbent precursor obtained in this step can be dried using a conventionally known method. For example, air drying, heat drying, reduced pressure drying, or a combination of these methods can be used. The drying temperature is preferably 150°C or less.

[0030] [(3) Firing process] In this step, the adsorbent precursor obtained in the previous step is calcined at a temperature of 300° C. or more and 500° C. or less to obtain an adsorbent. In this step, the adsorbent precursor can be calcined using a conventionally known calcination furnace. The calcination temperature is preferably in the range of 300° C. or more and 450° C. or less, more preferably in the range of 300° C. or more and 400° C. or less. The calcination time is preferably in the range of 1 hour or more and 48 hours or less, more preferably in the range of 1 hour or more and 24 hours or less, and particularly preferably in the range of 1 hour or more and 12 hours or less.

[0031] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0032] [Measurement method or evaluation method] The various measurements and evaluations were carried out as follows.

[0033] [1] Composition analysis (Zn, Ca, Al, Si) After crushing the adsorbent into powder, the sample was placed in a pressure molding ring and pressure molded for 3 minutes at a molding pressure of 30 MPa. The molded sample was set in an X-ray fluorescence analyzer (ZSX100e, manufactured by Rigaku Corporation) and measured by order (semi-quantitative) analysis. The amount of silicon was calculated by balance. Specifically, it was calculated by the following formula: Si(mass%)=100-Zn(mass%)-Ca(mass%)-Al(mass%) From the obtained compositions, Ca / Al 2 The molar ratio and Zn / Si molar ratio were calculated.

[0034] [2] Specific surface area Approximately 30 mL of the adsorbent was placed in a porcelain crucible (B-2 type), heated at 110°C for 1 hour, and then cooled to room temperature in a desiccator to obtain a measurement sample. Next, 1 g of this measurement sample was taken and the specific surface area (m 2 / g) was measured by the BET method.

[0035] [3] Pore volume The pore distribution of the adsorbent was measured under the following conditions using mercury intrusion porosimetry: The pore distribution of this measurement sample was measured under the following conditions. Pore ​​size distribution measuring device: PM-33GT1LP (QUANTA CROME) Pretreatment: 110℃ - 1 hour Sample volume: 3g Pore ​​size measurement range: 5nm~5000nm Contact angle of mercury: 150° Surface tension of mercury: 480 dyn / cm From the obtained pore distribution, the total volume of pores having a pore diameter in the range of 5 nm to 5000 nm was determined as the pore volume.

[0036] [4] Bulk density The packed bulk density (ABD) was calculated by dropping 50 g of adsorbent into a 250 ml measuring cylinder under its own weight from the top opening and measuring the volume (V 1 ) was measured and calculated using the following formula: Packed bulk density (ABD) (g / ml) = 50 / V 1

[0037] [5] X-ray diffraction measurements The adsorbents obtained in the examples were pulverized into powder form, and then subjected to powder X-ray diffraction measurement under the following conditions. <Condition> X-ray diffraction equipment: MiniFlex600 (Rigaku Corporation) Radiation source: Cu-Kα radiation Acceleration voltage, current: 40 kV, 15 mA Receiving slit: 10mm Scan speed: 10.0° / min Step width: 0.02° Measurement range (2θ): 5~90°

[0038] [6] Halogen adsorption test 15 ml of adsorbent and 15 ml of 2 mmφ glass beads were mixed and packed into a 27 mmφ reaction tube. Nitrogen gas was passed through this reaction tube at a flow rate of 150 ml / min. Then, the temperature of the packed bed was raised to 250 ° C. After the temperature stabilized at 250 ° C, the flow rates of nitrogen gas and HCl were changed to 150 ml / min and 150 ml / min, respectively, and chlorine was adsorbed for 90 minutes. Then, the flow rate of HCl was changed to 0 ml / min and the mixture was cooled to room temperature. After cooling, when the adsorbent was removed from the reaction tube, the presence or absence of adhesion (deliquescent) of the adsorbent was visually confirmed. Then, the adsorbent was removed and the glass beads were separated. Cl content was extracted from the obtained adsorbent, and the Cl concentration in the adsorbent was determined by coulometric titration.

[0039] [Example 1] 1043 g of zinc oxide (AZO-900J, manufactured by Hakusui Tech Co., Ltd.), 240 g of calcium aluminate (Alumina Cement No. 1, manufactured by Denka Co., Ltd.), and 842 g of amorphous silica (Toxsil 928, manufactured by Oriental Silicas Corporation) were added with 1000 g of ion-exchanged water and thoroughly kneaded in a kneader to obtain a clay-like precursor for molding. This precursor was molded in an extrusion molding machine, dried in an electric dryer at 120°C for 12 hours, and cut to a length of about 7 mm. Next, it was baked at 380°C for 4 hours to obtain a cylindrical adsorbent with a diameter of 2.6 mmφ and a height of 7 mm. The above-mentioned measurements and evaluations [1] to [6] were performed on this adsorbent. The results are shown in Table 1. The X-ray diffraction pattern obtained in the measurement of [5] is shown in Figure 1.

[0040] [Example 2] An adsorbent was obtained in the same manner as in Example 1, except that in the extrusion molding step, a precursor for molding was obtained using 761 g of zinc oxide, 200 g of calcium aluminate, 1158 g of amorphous silica, and 997 g of ion-exchanged water. This adsorbent was subjected to the measurements and evaluations of [1] to [6] above. The results are shown in Table 1.

[0041] [Example 3] An adsorbent was obtained in the same manner as in Example 1, except that in the extrusion molding step, a precursor for molding was obtained using 1,413 g of zinc oxide, 200 g of calcium aluminate, 526 g of amorphous silica, and 1,007 g of ion-exchanged water. This adsorbent was subjected to the measurements and evaluations of [1] to [6] above. The results are shown in Table 1.

[0042] [Comparative Example 1] An adsorbent was obtained in the same manner as in Example 1, except that in the extrusion molding step, amorphous silica was not added, and a molding precursor was obtained using 1870 g of zinc oxide, 280 g of calcium aluminate, and 1012 g of ion-exchanged water. This adsorbent was subjected to the measurements and evaluations of [1] to [6] above. The results are shown in Table 1.

[0043] [Comparative Example 2] An adsorbent was obtained in the same manner as in Comparative Example 1, except that in the extrusion molding step, a precursor for molding was obtained using 1261 g of zinc oxide, 840 g of calcium aluminate, and 989 g of ion-exchanged water. This adsorbent was subjected to the measurements and evaluations of [1] to [6] above. The results are shown in Table 1.

[0044] [Comparative Example 3] 1870 g of zinc oxide (AZO-900J, manufactured by Hakusui Tech Co., Ltd.), 184.2 g of calcium hydroxide (CH-2N, manufactured by Ube Materials, Ltd.), 192 g of pseudoboehmite alumina powder (AP-1, manufactured by JGC Catalysts and Chemicals Co., Ltd.), and 1012 g of ion-exchanged water were added and thoroughly kneaded in a kneader to obtain a clay-like precursor for molding. This precursor was molded in an extrusion molding machine, dried in an electric dryer at 120°C for 12 hours, and cut to a length of approximately 7 mm. Next, it was baked at 380°C for 4 hours to obtain a cylindrical adsorbent with a diameter of 2.6 mmφ and a height of 7 mm. The above-mentioned measurements and evaluations [1] to [6] were performed on this adsorbent. The results are shown in Table 1.

[0045] [Table 1]

[0046] 1, a peak attributed to calcium aluminate was confirmed in the X-ray diffraction pattern of Example 1. On the other hand, no peak attributed to calcium aluminate was confirmed in the X-ray diffraction pattern of Comparative Example 3.

Claims

1. Contains zinc as a component that adsorbs halogens, Contains calcium aluminate and silica, Halogen adsorbent.

2. Ca / Al 2 2. The halogen adsorbent of claim 1, wherein the molar ratio is 1.5 or less.

3. The Si content is SiO 2 The halogen adsorbent according to claim 2, wherein the halogen content is in the range of 10 mass % or more and 60 mass % or less in terms of halogen content.

4. 4. The halogen adsorbent according to claim 3, wherein the Zn content is in the range of 30 mass % or more and 80 mass % or less in terms of ZnO with respect to the total amount of the halogen adsorbent.

5. The sum of the Ca content and the Al content is calculated as CaO and Al content, respectively, based on the total amount of the halogen adsorbent. 2 O 3 The halogen adsorbent according to claim 4, wherein the halogen content is in the range of 5 mass % or more and 40 mass % or less in terms of halogen content.

6. 6. The halogen adsorbent according to claim 5, having a pore volume measured by mercury intrusion porosimetry in the range of 0.45 mL / g or more and 1.0 mL / g or less.

Citation Information

Patent Citations

  • Chlorine compound remover and method for removing chlorine compound from hydrocarbon fluid by using same

    JP2001072984A

  • Method for removing chloride and chloride absorbent

    JP2008184512A

  • Chemical absorbent composition

    JP2018523572A

  • Chlorine compound adsorbent

    JP2021007937A